Sustainable Tourism Marketing Through Destination Image: An AHP Approach for UNESCO Creative Cities in Gastronomy—The Case of Popayán, Colombia - Pablo Henrique de Oliveira Moreira; Carla Fraga; Joice Lavandoski; Paulo Almeida; Lucília Cardoso (Administrative Sciences)
Popayán (Colombia) was the first city to be designated a UNESCO Creative City of Gastronomy in 2005, positioning itself as a symbolic ‘myth of origin’ within the network. In the context of growing demands for local strategies aligned with the Sustainable Development Goals (SDGs), it is pertinent to understand how founding cities manage and project their image through sustainable tourism marketing. Almost two decades later, this study examines how Popayán communicates and sustains its image within the UNESCO Creative Cities Network (UCCN), guided by sustainable tourism marketing principles. Methodologically, the study adopts an exploratory and descriptive case study approach, based on documentary analysis of institutional sources and the application of the adapted Analytic Hierarchy Process Image—UNESCO Creative City Gastronomy (AHPI-UCCG) model. The results provided the following: (1) a multidimensional analysis of Popayán’s image in the context of sustainable marketing; (2) an assessment of how the city’s image responds to current branding challenges, using the adapted AHPI-UCCG model; and (3) a proposal for a context-sensitive investment agenda aligned with sustainability objectives. These results support the development of a personalised strategy for Popayán and demonstrate the potential of this approach to inform analyses of other Creative Cities of Gastronomy, while recognising the unique symbolic role of Popayán as the foundational case.